Novel exomphalos genetic mouse model: The importance of accurate phenotypic classification - Carnaghan, Helen (Saunders, 2013)
BACKGROUND: Rodent models of abdominal wall defects (AWD) may provide insight into the pathophysiology of these conditions including gut dysfunction in gastroschisis, or pulmonary hypoplasia in exomphalos. Previously, a Scribble mutant mouse model (circletail) was reported to exhibit gastroschisis. We further characterise this AWD in Scribble knockout mice. METHOD: Homozygous Scrib knockout mice were obtained from heterozygote matings. Fetuses were collected at E17.5–18.5 with intact amniotic membranes. Three mutants and two control fetuses were imaged by in amnio micro-MRI. Remaining fetuses were dissected, photographed and gut length/weight measured. Ileal specimens were stained for interstitial cells of Cajal (ICC), imaged using confocal microscopy and ICC quantified. RESULTS: 127 fetuses were collected, 15 (12%) exhibited AWD. Microdissection revealed 3 mutants had characteristic exomphalos phenotype with membrane-covered gut/liver herniation into the umbilical cord. A further 12 exhibited extensive AWD, with eviscerated abdominal organs and thin covering membrane (intact or ruptured). Micro-MRI confirmed these phenotypes. Gut was shorter and heavier in AWD group compared to controls but morphology/number of ICC was not different. DISCUSSION: The Scribble knockout fetus exhibits exomphalos (intact and ruptured), in contrast to the original published phenotype of gastroschisis. Detailed dissection of fetuses is essential ensuring accurate phenotyping and result reporting.